Media sosial dalam pembelajaran kosakata bahasa inggris: Perspektif mahasiswa non-bahasa - Agus Wilson; Dian Novita; Septian Wulandari (SAP (Susunan Artikel Pendidikan), 2025)
This study aims to analyze the perceptions of non-English major students regarding the use of social media in English vocabulary learning and to evaluate the influence of five key social media factors on their perceived effectiveness. A descriptive-correlational quantitative approach was employed, involving 175 first-semester students of Indraprasta PGRI University, Jakarta, who completed an online Likert-scale-based questionnaire. Descriptive analysis showed that students had a positive perception of social media use, with ease of access and navigation (M = 23.08) and constructive feedback (M = 23.05) receiving the highest average scores. Spearman correlation tests revealed that all five factors had a positive and significant relationship with perceived effectiveness, with the strongest correlation found in ease of access and navigation (rₛ = 0.343), followed by constructive feedback (rₛ = 0.324) and interactivity (rₛ = 0.317). These findings confirm that social media has the potential to serve as an effective vocabulary learning tool when designed with attention to accessibility, feedback support, and active engagement. This study provides practical contributions for educators and content developers in designing engaging, safe, and discipline-relevant social media learning strategies.